Pengembangan Freeze Vacuum Drying Dengan Sistem Kendali Menggunakan Reverse Valve - Martin, Awaludin; Hermanto, Jheri; Agustina, Dinni; Surianto, Muhammad Akbar; Putri, Sunny Ineza; Khotimah, Nur (TURBO [Tulisan Riset Berbasis Online], 2024)
The post-harvest handling process for rice aims to reduce the water content of rice grain, one of which is using the drying method. To maintain the quality of grain, evaluation and corrections are needed in handling so that losses can be minimized. Mechanical drying methods such as freeze drying are an effective vacuum solution, because they combine freeze drying and vacuum drying which have advantages in efficiency and quality of results. This vacuum dryer prototype has a maximum capacity of 10 kg of rice, the refrigerant used is R-134a, and the vacuum pressure that can be achieved is 5 bar below atmospheric pressure. This research will use variations in mass of 1 kg, 5 kg, and 10 kg, then the mass of 10 kg will be varied with refrigerant pressure of 14 bar, 15 bar, and 16 bar. The results of this test are that for the mass variation of 1 kg the air content that can be removed is 89% for 12.1 hours, for the mass of 5 kg the air content that can be removed is 85% for 15.3 hours, and for the mass of 10 kg the air content that can be removed is 76% for 17.5 hours. For variations in refrigerant pressure at a pressure of 16 bar 78% of the air content is lost for 19.8 hours, 15 bar 76% of the air content is lost for 19 hours, and 14 bar 62% of the air content is lost for 18 hours